Inhabiting institutions: Shaping the first teacher role in Swedish schools. Issue 1 (29th January 2019) - Alvehus, Johan; Eklund, Sanna; Kastberg, Gustaf
Abstract: This study examines a recent reform in the Swedish teaching profession—the so-called first teacher reform, aimed at increasing teacher professionalism and the status of teachers. The reform created a situation by which a new role had to be created and inhabited by first teachers, appointed on what were considered arbitrary criteria. There were few existing norms, rules, and routines to draw upon for the newly appointed first teachers. The empirical focus of this study, based upon interviews and observations from seven schools in four Swedish municipalities, is how the newly appointed first teachers shape their role in relation to other teachers and to school management. We contribute to inhabited institutions theory by showing how processes of institutional change rely on externalization by relational work, through which the new role gains legitimacy and mutual recognition, and on objectification by jurisdictional work, through which the new role becomes taken for granted in a new division of labour. We thus argue that changes in the material basis of work processes are key to understanding processes of institutional inhabitation. Moreover, we show how changes in intra-professional jurisdictions can lead to upgrading, rather than degradation, of professional work.